DEVELOPMENT OF DISASTER MITIGATION-BASED MATHEMATICS LEARNING MATERIALS TO ENHANCE MATHEMATICAL APPLICATION SKILLS AMONG JUNIOR HIGH SCHOOL STUDENTS IN PIDIE JAYA - Zulfikar; Khairul Ismi; Siti Rahmatina (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2026)
Indonesia is a disaster-prone country that requires the strengthening of disaster mitigation education from an early age, including through school-based learning. The abstract nature of mathematics often causes students to struggle with applying mathematical concepts to real-world situations. This study aims to develop disaster mitigation-based mathematics learning materials and to test their feasibility and effectiveness in improving the mathematical application skills of junior high school students in Pidie Jaya Regency. This study employed the Research and Development (R&D) method using the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects were junior high school students in Pidie Jaya Regency. Research instruments included an expert validation sheet, a student response questionnaire, and a mathematical application skills test. Data were analyzed descriptively to determine the validity and practicality of the media, and gain score analysis was conducted to assess the effectiveness of the learning media. The results indicate that the disaster mitigation-based mathematics learning media falls into the “feasible” to “highly feasible” categories. Student responses were positive, and test results showed an improvement in students’ mathematical application skills after using the learning media. Thus, the developed learning media is effective as an alternative for contextual learning and supports disaster mitigation education in schools.